Kajian Sifat Fisikokimia dan Organoleptik Cookies Rempah Dengan Penambahan Ekstrak Daging Buah Pala (Myristica fragrans) - Latulanit, Nabila Shellawaty; Albaar, Nurjanna; Rasulu, Hamidin; Ibrahim, Abu Rahmat; Wulansari, Angela (Cannarium, 2021)
Extract from the nutmeg flesh can be used as an additional ingredient in making cookies spice. cookies Spiceare food products that are dried by oven. cookies Spiceare made from wheat flour, sugar and butter with a moisture content of less than 5% and can be stored for quite a long time. This study aims to determine the formulation for making cookies spicewith the addition of the best nutmeg pulp extract. This research method was completely randomized design (CRD) with a single factor, namely the addition of nutmeg pulp extract with 5 treatment levels and 3 replications to obtain 5x3 = 15 experimental units. The treatments consisted of 5 treatments, namely 0% nutmeg and 100% wheat flour (P0), 10% nutmeg pulp and 90% wheat flour (P1), 20% nutmeg pulp and 80% wheat flour. (P2), 30% nutmeg pulp and 70% wheat flour (P3), and 40% nutmeg pulp and 60% wheat flour extract formulation (P4). Parameters covering chemical properties analysis include: moisture content, ash content, protein, carbohydrate, fat, and antioxidant tests. While the organoleptic test analysis includes: taste, texture, color, and aroma. The best treatment was found in the formulation of 40% nutmeg pulp and 60% wheat flour in treatment P4.Ã‚Â